Forum Panelist 4: COVID-19 Response: Speaking for the Unspoken for - Balasundaram, Susheela R (International Journal of Human and Health Sciences (IJHHS), 2021)
The COVID-19 pandemic has brought about unparalleled changes in all our lives, on an individual, societal and global level that it draws us into a necessary reflection of how we have lived our lives as an individual, a community and ashumankind. As health practitioners, we need to appraise our ways of working and have the courage to speak and call for the change we want to see. A time for an honest examination of policies of exclusion and marginalization of any sections of populations, and consequences of such policies in the face of a pandemic. A time for health professionals and those who speak for the unspoken to rise to the forefront with the right intention at heart, to set the right knowledge to action in moving towards a more inclusive and resilient health system. If we continue in our old ways, the lesson will be lost on us and this may be the pandemic that deepens the divide, which will be to our own detriment. Balancing the priorities in public health, and the politico-socio-economic priorities of a nation, what path would best address these priorities? As there are challenges, there are opportunities to have inclusive policies, coordinated health programming, with collaborative efforts in strengthening preparedness and response mechanisms, engaging the public, civil society, academia, international organizations and private sectors. International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S9